The Effect of Competence, Emotional Intelligence and Work Environment on Employee Performance - Amnah Hadi; St. Syahriati St. Syahriati; St. Hatidja St. Hatidja; Aditya Halim Perdana Kusuma Putra (International Journal of Artificial Intelligence Research, 2022)
This study was conducted with the aim of knowing and analyzing the effect of competence, emotional intelligence, work environment on the performance of employees of PT. Angkasa Pura IV Makassar and to analyze the variables that have the most influence on the performance of employees of PT. Angkasa Pura IV Makassar. This study chose the object of research to employees of PT. Angkasa Pura IV Makassar and data collection was carried out with primary data and secondary data with sampling methods using the slovin technique, namely 68 respondents from a population of 211 employees. The results of research on competency variables, emotional intelligence and work environment simultaneously have a positive and significant effect on employee performance. Competency variables partially have a negative but insignificant effect on employee performance, emotional intelligence variables partially have a positive and significant effect on employee performance while work environment variables partially have a positive and significant effect on the performance of employees of PT. Angkasa Pura IV Makassar. Data processing using multiple regression with spss version 26. This writer suggests that employees of PT. Angkasa Pura IV Makassar. further improve the Kempetensi variable and emotional intelligence to improve employee performance. and for other researchers to continue this research so that the limitations in this study can be refined